PENGOLAHAN PUPUK ORGANIK CAIR BERBAHAN DASAR LIMBAH SAYURAN DI DESA SUMBER BENING KECAMATAN SELUPU REJANG KABUPATEN REJANG LEBONG PROVINSI BENGKULU - Linna Fitriani; Destien Atmi Arisandy (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2020)
Agricultural production in the Selupu Rejang Subdistrict is large enough in quantity to become a center for sending agricultural products to various regions in Indonesia. High market demand makes groups of farmers use a variety of ways to increase agricultural production. This PKM program can provide solutions to the problem of the availability of increasingly scarce fertilizers as well as the problem of declining soil fertility. The program also increases knowledge about processing techniques and adds economic income to agricultural groups in processing liquid organic fertilizer based on vegetable waste. In addition, this program is able to encourage partners, especially agricultural groups to switch to oragnic agriculture that reduces funding for fertilizer use and can make the land on agricultural land rejuvenated and fertile so that it supports the agriculture of the area. Keywords: Vegetable waste, Liquid organic fertilizer